A review of the burden of disease due to otitis media in the Asia-Pacific - Mahadevan M. (2017)
Objective: The burden of disease due to otitis media (OM) in Asia Pacific countries was reviewed to increase awareness and raise understanding within the region. Methods: Published literature and unpublished studies were reviewed. Results: In school-age children, OM prevalence varied between 3.25% (Thailand) and 12.23% (Philippines) being highest (42%) in Aboriginal Australian children. OME prevalence at school age varied between 1.14% (Thailand) and 13.8% (Malaysia). Higher prevalence was reported in children with hearing impairment, HIV, pneumonia and rhinitis. CSOM prevalence was 5.4% in Indonesia (all ages), 15% in Aboriginal Australian children and 2-4% in Thailand, Philippines, Malaysia and Vietnam (WHO estimate). OM prevalence/incidence and service utilisation were highest in children 2-5 years of age. The disease burden was substantially higher in Pacific Island children living in New Zealand (25.4% with OME), and was highest in indigenous Australians ( > 90% with any OM). Streptococcus pneumoniae and Haemophilus influenzae dominated as primary causes of AOM in all studies. Few studies examined pneumococcal serotype distribution. Health-related cost estimates for OM, when available, were substantial. In developing countries, significant investment is needed to provide facilities for detection and treatment of ear disease in children, if long term hearing deficits and other sequelae are to be prevented. Conclusion: The available evidence suggests an important burden of disease and economic cost associated with OM in most Asia Pacific countries and a potential benefit of prevention through vaccination. Large, prospective community-based studies are needed to better define the prevalence of ear disease in children, and to predict and track pneumococcal conjugate vaccine impacts. AOM prevention through vaccination may also provide a means of reducing antibiotic use and controlling antibiotic-resistant disease in children. This review highlights the need for additional research, and provides a basis on which to build and develop regional guidelines for OM management. © 2012 Elsevier Ireland Ltd.